Performing the past : memory, history, and identity in modern Europe - Tilmans, Karin; Vree, Frank van; Winter, J. M. (Amsterdam University Press, 2010)
Performing the Past is an investigation of the multiple social and culture practices through which Europeans have negotiated the space between their history and their memory over the past 200 years. In museums, in opera houses, in the streets, in the schools, in theatres, in films, on the internet and beyond, narratives about the past circulate today at a dizzying speed. Producing and selling them is big business; if the past is indeed a foreign country, there are tens of thousands of tourist agents, guides, and pundits around to help us on our way, for a fee, to be sure.